Misie a smysl misijní činnosti v raně koloniální Brazílii optikou kroniky História do Brasil Vicenteho ze Salvadoru - Kalenda, František (Lidé města, 2015)
While Jesuit missions and missionary activities in early Colonial Brazil have been thoroughly studied both in the Czech Republic and elsewhere, Franciscan missionaries hailing from the period leading up to the 1630 destruction of the Olinda Centre are often forgotten or left for the historians of the Franciscan Order to deal with. A striking lack of primary Franciscan period sources on the subject is partially responsible for this state; the vast majority of available Franciscan primary sources date from a much later period, to the 18th century. The completely preserved and not thoroughly studied História do Brasil by Vicente of Salvador, a Franciscan custodian and historiographer from 1630, is therefore a unique source of information on the Franciscan order in Brazil and its missionary activities in this Portuguese colony. Although missions and not even Vicente’s order itself are not in the epicentre of the chronicle, it contains both practical information on the Franciscan activities on Brazilian soil and, maybe even more importantly, a specific point of view on the meaning of missions to the indigenous population. Unlike his Jesuit contemporaries and Franciscan colleagues from a later period, Vicente of Salvador does not provide a particularly successful narrative of missionary activities, and remains rather sceptical about the potential of christianising “gentiles”. Instead, he sees indigenous Brazilians as widely incapable of becoming Christians, and favours force and even defends enslavement as an alternative to “peaceful” missions. These views, differing from the other contemporary Jesuit sources and the later Franciscan chroniclers, being much closer to the view of colonists, make his account even more fascinating and attention-worth.